Sistema web de gestión administrativa en la operadora turística Ecuador fourexperiences s.a. de la ciudad de Chone provincia de Manabí - Loor Rodríguez, José Gabriel (2015)
This work was performed with the purpose of developing and implementing a Web application for monitoring reservations and information handled by the tour operator Ecuador FourExperiences SA being an important communication media between client and the company helping booking process circuit, orders and travel to Galapagos. The methodology used in the project known as MIDAS (Interactive Development Methodology Applications Software). Which it is based on models for development using WIS (Web Information Systems), such models were developed in phases or prototypes that were delivered to customers in the system to validate the results of development. With the completion and implementation of the system that will be able to streamline processes and optimize the time that the client used to make a reservation, as the manual processes required more time to complete, plus how to present clients with detailed information improved circuits and travel features. Upon completion of this work the authors conclude that the methods and techniques used were adequate for the proper design of the database and the interfaces used in development environments were of great importance to implement the web system.